1997
DOI: 10.1002/(sici)1097-0231(199704)11:6<551::aid-rcm914>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation Ion Trap Mass Spectrometry—Storage Field Suppression and its Effect Upon Analytical Performance

Abstract: The combination of laser desorption and ablation with mass spectrometry has been, and will continue to be, a useful marriage of technologies. Quadrupole ion trap mass spectrometry, which has evolved from a simple mass selective detector for gas chromatography to a high performance analytical tool over the last decade, is being coupled more frequently with desorption sources, such as lasers and particle beams. The present work addresses a shortcoming of the use of laser sampling with quadrupole ion traps: laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We found that a compatible ion source can be obtained through a laser ablation method, which was demonstrated in earlier experiments. 9,10,11,12,13 Though care must be taken to provide appropriate thermal anchoring and isolation, it is possible to use all conventional ion sources, including photoionization and electron impact ionization of atoms produced by an oven. In this paper we focus on laser ablation because it is simple and able to load a variety of species.…”
Section: Introductionmentioning
confidence: 99%
“…We found that a compatible ion source can be obtained through a laser ablation method, which was demonstrated in earlier experiments. 9,10,11,12,13 Though care must be taken to provide appropriate thermal anchoring and isolation, it is possible to use all conventional ion sources, including photoionization and electron impact ionization of atoms produced by an oven. In this paper we focus on laser ablation because it is simple and able to load a variety of species.…”
Section: Introductionmentioning
confidence: 99%